PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - Surjadi, Julisar; Anggraini, Stela (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study is to obtain empirical evidence on the effect of audit committees, investment decisions, fiscal loss compensation, corporate social responsibility, profitability, and leverage on tax avoidance. This study uses samples from all consumer non-cyclicals and consumer cyclicals companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022 with 59 companies used for sample in this research. This sample selection used purposive sampling method with research data totaling to 177 and using multiple linear regression for hypothesis testing. The results of this study showed that leverage has a positive effect on tax avoidance, profitability has a negative effect on tax avoidance while the other variables which is audit committee, investment decisions, fiscal loss compensation, and corporate social responsibility had no effect to tax avoidance.